Hankel Operators with Weighted Lipschitz Symbols in the Unit Ball - Sehba, Benoît F.; Tchoundja, Edgar (Mathematica Scandinavica, 2013)
We characterize symbols of bounded Hankel operators between some Hardy-Orlicz spaces and usual Hardy spaces in the unit ball of $C^n$.